(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of this work was to improve on the solubility of ibuprofen using two vegetable oil-based self-emulsifying formulations (SEFs) and to evaluate the potential usefulness of CarbosilÂ® (CARB) and Landolphia owariensis latex (LOL) in them. Isotropicity, drug solubility, viscosity, emulsification time (EMT), drug release, aqueous dilution, postemulsification drug precipitation and refrigeration tests were carried out on the coconut oil (CO) and shea butter oil (SBO)-based SEFs. Results showed that only four out of nine batches of the SEFs passed the preformulation isotropicity test. A 100-mg quantity proved to be the maximum amount of drug that could be dissolved by the SEFs to form a stable solution. After 72 hrs all the SEFs still retained stability. All of CO SEFs witnessed remarkable phase separation or drug precipitation However, SBO SEFs having oil:surfactant:cosurfactant ratio of 35:45:20 and containing LOL or LOL-CARB blend lost isotropicity or displayed drug precipitation 6 months later. Refrigeration temperature did not introduce any form of instability or phase separation. Similar viscosities were recorded by the two oil-based SEFs. However, little but inconsistent variation in viscosity was observed between SBO SEFS and LOL-containing SEFs. Aqueous dilution and postemulsification drug precipitation test indicated absence of phase separation and drug precipitation, respectively. Drug-release studies showed that the t50 of SBO SEFs almost ranked equally with SBO SEFs containing LOL. CO SEFs emulsified at a longer time than those of SBO. SEFs distinctly recorded higher EMTs than those with LOL or CARB-LOL blend. In conclusion, solubility of ibuprofen was improved, CARB gelled the SEFs while LOL reduced their EMTs.